PERANCANGAN BRANDING KELURAHAN KARANGSARI BERBASIS AGROWISATA UNTUK MENGENALKAN IDENTITAS KAMPUNG BELIMBING KOTA BLITAR - Alfathan, Ika; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
Agrowisata Belimbing Karangsari is one of the tourist destinations nature family is interesting to visited who are located in the Blitar. Here travelers can pluck and eat directly starfruit from the garden. Agrowisata Belimbing Karangsari located in the Karangsari Village, wherein all citizens of the Karangsari Village starfruit tree planted in the garden of their home. Agrowisata Belimbing Karangsari continue to make improvements and the construction of supporting facilities in agrotourism. But, the existence of Agrowisata Belimbing Karangsari not well known by the public because they at least used promotional media. Therefore, to attract the attention of the public requires a strategy of branding and promotion of effective and efficient to provide clear information and introduce the advantages of starfruit that is owned by the Karangsari Village. So hopefully with their branding design is expected to introduce identity Starfruit Village Karangsari as the hometown of Blitar. It can also attract and encourage people to visit the Agrowisata Belimbing Karangsari located in the Karangsari Village. Keywords : Branding, Promotions, Identity, Belimbing, Karangsari Village, Agrowisata Belimbing Karangsari